Potential Pseudomonas Isolated from Soybean Rhizosphere as Biocontrol against Soilborne Phytopathogenic Fungi - ARI SUSILOWATI; ARIS TRI WAHYUDI; YULIN LESTARI; ANTONIUS SUWANTO; SURYO WIYONO (Bogor Agricultural University, Indonesia, 2011)
Plants are liable to be attacked by soilborne fungal pathogens which are responsible to reduce plant growth and losses in yield. In Indonesia, indigenous soybeans’ rhizobacteria such as antifungal producing Pseudomonas sp. have not many been reported yet. Therefore, the potential of the Pseudomonas sp. as biocontrol agent should be deeply explored. The aim of this study was to screen the indigenous soybeans’ rhizobacteria Pseudomonas sp. that possessing biocontrol characters against soilborne mainly i.e. Sclerotium rolfsii, Fusarium oxysporum, and Rhizoctonia solani, in vitro and in planta. Eleven isolates identified Pseudomonas sp. CRB numbered by CRB-3, CRB-16, CRB-17, CRB-31, CRB-44, CRB-75, CRB-80, CRB-86, CRB-102, CRB-109, and CRB-112 were affirmed to be candidates of biocontrol agents toward the soilborne fungal pathogens. Pseudomonas sp. CRB inhibited growth of the pathogenic fungi approximately 11.1-60.0% in vitro. Among of them, 7 isolates were also produced siderophore, 2 isolates produced chitinase, and 4 isolates produced hydrogen cyanide. Seed coating with the Pseudomonas sp. CRB accomplished disease suppression in planta about 14.3-100% in sterile soil condition and 5.2-52.6% in non sterile soil condition. Consistency in high performance more than 30% of disease suppression in non sterile soil condition suggested that 5 isolates i.e. CRB-16, CRB-44, CRB-86, CRB-102, and CRB-109 isolates have great promising to be developed as biocontrol agents of soilborne pathogenic fungi.